ANALYSIS OF THE IMPLEMENTATION OF E- BANKING IN MONTENEGRO DURING PANDEMICS - Perović, Nataša; Abramović, Nikola; Vukčević, Nikola; Ristanović, Bojana (Economic Outlook, 2022)
Fast development of information and communications technology also resulted in dynamic changes in banking sector. The subject of this paper is the analysis of electronic banking presence among bank clients in Montenegro. Additionally, the paper shall present the data on the use of computers and internet access in companies and at home as well as data on use of internet and mobile banking with the reference to their trends in previous years. The objective of the paper is to determine and show the advantages of the application of electronic banking both for the banks and their clients where the data from 2020 shows that during coronavirus pandemic, the number of e-banking service users in the country has grown considerably. Having in mind that electronic banking impacts the efficiency and speed of business operations between banks, banks and clients, as well in banks themselves, it is necessary to consider factors of poorer presence of Internet and mobile banking in Montenegro in comparison to other highly developed countries in Europe so that the access to and their application would improve and be more represented.
Keywords: banks; e-banking; internet and mobile banking; technological changes; Information and Communications Technology (ICT)